2020
DOI: 10.24075/brsmu.2020.036
|View full text |Cite
|
Sign up to set email alerts
|

IgM and IgG antibodies against SARS-CoV-2 in neonates born to mothers with COVID-19

Abstract: Immunity against the novel coronavirus infection in neonates born to mothers with PCR-confirmed COVID-19 is an understudied field of research. The aim of this study was to analyze the levels of IgM and IgG antibodies against SARS-CoV-2. The study was carried out in 20 mothers aged 19 to 39 years and 21 neonates (including a pair of twins). Babies born to mothers with elevated IgM and IgG against SARS-CoV-2 also had elevated IgG. There is a hypothesis that anti-SARS-CoV-2 IgM are not passed on to the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In total, the studies reported findings from 325 women whose pregnancy outcome was known following SARS-CoV-2 infection, seven of which were twin pregnancies [ 25 , [31] , [32] , [33] , [34] , [35] ], six pregnancies were terminated (one for maternal health reasons [ 18 ], one for personal reasons [ 19 ], three for “personal choice” [ 21 ] and one where the reason was unclear [ 17 ]). Of the remaining pregnancies, 83 births (58%) were by Caesarean section and no information was provided in 16 cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, the studies reported findings from 325 women whose pregnancy outcome was known following SARS-CoV-2 infection, seven of which were twin pregnancies [ 25 , [31] , [32] , [33] , [34] , [35] ], six pregnancies were terminated (one for maternal health reasons [ 18 ], one for personal reasons [ 19 ], three for “personal choice” [ 21 ] and one where the reason was unclear [ 17 ]). Of the remaining pregnancies, 83 births (58%) were by Caesarean section and no information was provided in 16 cases.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 167 infants were born after 37 weeks' gestation, and 58 were born preterm (including four sets of twins), with the majority being born after 30 weeks' gestation. Seven infants were born in the “third trimester” (not defined by studies) and the exact gestation of 95 infants was unclear [ 17 , 25 , 35 ], with one study providing median gestational ages and the interquartile range which included four multiple-pregnancies [ 25 ]. There were six terminations of pregnancy including one at 22 weeks' gestation [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation